Negative thermal expansion and electrical properties of α-Cu2V2O7. Issue 11 (September 2016) - Zhang, Niu; Li, Li; Wu, Mingyi; Li, Yuxiang; Feng, Dongsheng; Liu, Cunyuan; Mao, Yanchao; Guo, Juan; Chao, Mingju; Liang, Erjun
Abstract: The orthorhombic copper(II) vanadate (α-Cu2 V2 O7 ) was synthesized using a solid state method, and its negative thermal expansion (NTE) and electrical properties were systematically studied. The results show that the α-Cu2 V2 O7 exhibits NTE property linearly from room temperature (RT) to 470 K with the coefficient of thermal expansion (CTE) −5.8 × 10 −6  K −1 . The coupling rotation of rigid unit modes (RUMs) caused by transverse vibrations of bridge oxygen atoms is attributed to the NTE behavior. Moreover, NTE property performs nonlinearity in 470–610 K, and the average CTE is about −2.4 × 10 −6  K −1 which is caused by the synthetic action of d 9 Jahn-Teller effect of Cu 2+ and small amount of micro-pores. The material exhibits low thermal expansion between 610 and 720 K with CTE 0.43 × 10 −6  K −1 . The distortion effect was confirmed by UV–vis absorption spectroscopy. The impedance spectroscopy analysis shows that the α - Cu2 V2 O7 has a certain semiconductor property, which is consistent with the results of ab-initio calculation. The NTE property and pyroconductivity bring a good potential application in composite conductive ceramic and high temperature conductive materials.